Imaging Linear Birefringence and Dichroism in Cerebral Amyloid Pathologies - Jin, Lee-Way; Claborn, Kacey A.; Kurimoto, Miki; Geday, Morten A.; Maezawa, Izumi; Sohraby, Faranak; Estrada, Marcus; Kaminksy, Werner; Kahr, Bart (Proceedings of the National Academy of Sciences - PNAS, 2003)
New advances in polarized light microscopy were used to image Congo red-stained cerebral amyloidosis in sharp relief. The rotating-polarizer method was used to separate the optical effects of transmission, linear birefringence, extinction, linear dichroism, and orientation of the electric dipole transition moments and to display them as false-color maps. These effects are typically convolved in an ordinary polarized light microscope. In this way, we show that the amyloid deposits in Alzheimer's disease plaques contain structurally disordered centers, providing clues to mechanisms of crystallization of amyloid in vivo. Comparisons are made with plaques from tissues of subjects having Down's syndrome and a prion disease. In plaques characteristic of each disease, the Congo red molecules are oriented radially. The optical orientation in amyloid deposited in blood vessels from subjects having cerebral amyloid angiopathy was 90° out of phase from that in the plaques, suggesting that the fibrils run tangentially with respect to the circumference of the blood vessels. Our result supports an early model in which Congo red molecules are aligned along the long fiber axis and is in contrast to the most recent binding models that are based on computation. This investigation illustrates that the latest methods for the optical analysis of heterogeneous substances are useful for in situ study of amyloid.